Kajian Pengaruh Penggunaan Zat Admixture ” X”, Fiber Dan Semen Grouting Terhadap Kuat Tekan Dan Retak Beton Pada Beton Tanpa Perawatan - Aland Surya Nugroho; Theovilla Arry (G-SMART, 2019)
At present, there are many damages to concrete structures in buildings that have build. One such damage is the appearance of cracks. Cracks in concrete are caused by many factors, including loads that exceed limits, temperature, components of the constituent material, the process of making concrete and time.This research was conducted with the aim of studying the effect of the use of admixture "x", fiber and cement grouting on the compressive strength and cracking of concrete in untreated concrete. The specimens in this study are in the form of a concrete slab with a size of 1 m × 1 m with a thickness of 6 cm, cylinder size Ø 15 cm with a height of 30 cm, concrete quality plan K 250 (20,75 MPa), viscocrete, fiber type monofilament polypropylene, and cement grouting.The results of this study indicate that the addition of fiber can minimize the appearance of cracks in concrete. In addition, it also increases the compressive strength of concrete, namely K 295 (24,5 MPa). The use of viscocrete actually causes the most cracks if not cured, but has the highest strength, namely K 340 (28,3 MPa).